STRATEGI PERSONALISASI PADA MOOC: TINJAUAN LITERATUR SISTEMATIS - Ilyas Khoirudin; Kurnia Khafidatur Rafiah; Muhammad Rifqi Arviansyah (STKIP PGRI Situbondo, 2025)
This study aims to identify personalization strategies in Massive Open Online Courses (MOOC) and evaluate their impact on learner engagement, completion rates, and learning outcomes. The research employs a Systematic Literature Review (SLR) using the PRISMA approach, with articles sourced from the Scopus database and selected based on relevance, publication type, and time range (2015–2024). From an initial 20,230 articles, a systematic screening process resulted in 34 articles included in the final analysis. The findings indicate that personalization strategies, such as adaptive learning pathways, AI-based recommendation systems, and learning analytics, contribute to enhancing the learning experience in MOOCs. However, their effectiveness depends on system design and learner characteristics. Additionally, challenges such as technological gaps and resource limitations remain major obstacles to implementation. This study provides insights for MOOC developers in designing more effective and inclusive learning systems.